PENGEMBANGAN WILAYAH LANGOWAN SEBAGAI KAWASAN AGROPOLITAN - Pingkan E. Dien; Ventje V. Rantung; Olly E. Laoh; Vicky R.B. Moniaga (COCOS, 2014)
ABSTRACTThis study aims to see / know the potential and regional development strategies as agropolitan Langowan. The objective of this research is to know the potency and the Langowan regional development strategy as an agropolitan region. The backround of this research is the disparity between village and city that result in bias urban process where the rural potency is absorbed based on human resource, natural resource and capital. The data used in this study is based on data for the analysis of agropolitan regional development using descriptive analysis, after potency analysis is is performed, the agropolitan regional development is established using SWOT analysis.The research result showed that the Langowan region is potential for agropolitan region supported by the potential of agro and politan and also based on internal and external matrix using horizontal integrated strategy by integrated strategy by increasing planting area and regional development position anaysis as agropolitan Langowan are in the first quadrant as a favorable situation in the SWOT analysis diagram